Algeria–Mali trade: the normality of informality. Issue 2 (3rd July 2017) - Bensassi, Sami; Brockmeyer, Anne; Pellerin, Mathieu; Raballand, Gaël
Abstract : This paper estimates the volume of informal trade between Algeria and Mali and analyzes its determinants and mechanisms, using a multi-pronged methodology. In addition to mirror statistics analysis, we provide evidence of the importance of informal trade, drawing on satellite images and surveys with informal traders in Mali and Algeria. We estimate that the weekly turnover of informal trade fell from approximately US2 million in 2011 to US0.74 million in 2014, but that trade continues to play a crucial role in the economies of northern Mali and southern Algeria. We also show that official trade statistics are meaningless in this context because they capture less than 3% of total trade. Meanwhile, profit margins of 20–30% on informal trade help to explain the relative prosperity of northern Mali. Informal trade probably plays a strong role in poverty reduction, especially in the Kidal region.